Strategi Pembelajaran Yesus Khotbah di Bukit Sebagai Refleksi Guru Masa Kini - Yonatan Alex Arifianto; Hana Hana (THEOLOGIA INSANI: Jurnal Theologia, Pendidikan, dan Misiologia Integratif, 2023)
The success or failure of an education is largely determined by the strategy used by each educator in teaching in order to obtain maximum results. Therefore the research aims to describe how the Jesus on the Mount Learning Strategy as a Reflection of Today's Teachers, by using descriptive qualitative methods it can be concluded that the learning strategy of Jesus preaching on the hill is a strategy that every teacher needs to have today, namely teachers who have the expertise, skills, creativity in teaching with the ability to utilize existing media in order to achieve effective, efficient and relevant learning, namely the material, points or values that the teacher wants to instill and teach can be conveyed, understood and students are able reflect on the lessons learned in everyday life. Today's teachers are expected to own and make the learning strategies that Jesus used when preaching on the hill as a reflection in teaching today. So that today's teachers can have accuracy, skill, skill, expertise in creating a learning atmosphere, the ability to convey learning material to students with maximum results and on target.